The Impact of Artificial Intelligence in Software Development - Silva, Ronald Augusto Domingos; Pires, Thalisson Lopes Gonçalves; Mendes, Rodrigo Jeremias; Matos, Mikaelly Elídia; de Oliveira, Kevenn Laranjeira; Soares, Liziane Santos (Anais do Workshop de Sistemas de Informação (WSIS); 2024: Anais do XV Workshop de Sistemas de InformaçãoDO - 10.5753/wsis.2024.33680, 2024)
The rise of Artificial Intelligence (AI) has brought significant transformations to software development and the job market. This study explores the integration of AI in various contexts within the Information Technology (IT) industry, including quality control, process automation, service management, and security. The analysis details how these technologies are reshaping traditional practices and redefining the roles of IT professionals. Additionally, the impact of AI on the job market is examined, highlighting automation of repetitive tasks, wage polarization, and the increasing demand for specialized skills. The research reveals that despite the challenges, AI adoption offers substantial opportunities to enhance efficiency and create new business models. The conclusion underscores the need for a strategic approach to AI implementation, balancing technological innovation with ongoing professional development and adaptation, ensuring an equitable and effective transition to a more automated and technologically advanced work environment.